Franchising: R&D analysis in Brazil and Poland - Sichel, Debora Lacs; Natividade da Costa, Joyce (Research Papers of Wrocław University of Economics, 2018)
The economic development is a consequence of the innovation procedure. This paper is about the innovation procedure in Brazil and in Poland. Both nations were redemocratized in the end of the 20th century. The similarities of both countries do not reflect the development of IP since Brazil has got difficulties as a consequence of its economic crisis. This crisis did not allow the establishment of R&D centres. The paper also analyses the Polish integration in the European Union and how it has enabled the establishment of R&D centres through the franchising
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 93-108
Keywords: economic development; franchising; innovation; research; trademarks; rozwój ekonomiczny; franczyza; innowacje; badania; znak towarowy